Exploring The Waste Management Policy in Developing Country: Lesson and Challenges from Kediri Regency, Indonesia - Sudrajad, Edi; Tjahjanulin, Domai; Mochamad, Makmur; Ima, Kumalasari (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2022)
In recent years, the problem of solid waste management has highlighted numerous discussions in public policy literature. This research is intended to explore the waste management policy in developing country to reflect on how the local government with their limited capacity and resources deal with solid waste problems. It is kind of descriptive research that is conducted through qualitative approach by using semi-structured interview. This inquiry has been conducted in Kediri Regency as one of developing region with growing GDRP over years in Indonesia. In addition, the analysis process of this research has applied an interactive model which is suitable to administer the narrative-based data. The result of this study has underlined two major information; first the implementation of waste management policy in Kediri Regency has facing several challenges including, limited resources, capacity and infrastructure; second, the local government manages to shift the strategy from conventional to collaborative model by highlighting the role of local civilians.